What is the Cost? The Effect of the Post-Independence Government on Public Sector Performance in Namibia - Shafuda, Christopher Pomwene; Kumar De, Utpal (Journal of Reviews on Global Economics, 2024)
The end of colonisation in Sub-Saharan Africa did not bring the expected welfare to many. Several governments stumbled with public resource mismanagement, which created room for corruption and other malpractices (Good, 1994: Maipose, 2000: Ncholo, 2000: Tsatsu, 2015). This article examines the performance and efficiency of the Namibian government interventions between 1990 and 2020. The findings reveal that some indicators showed significant improvement, while some did not record any substantial improvement. Decent performance was recorded in government policies to reduce inequality and poverty. Good performance is also seen in policies improving education attainment, while policies to reduce unemployment performed poorly. Other indicators have shown mixed results. The results also revealed the worst performance during the first five years after independence. The period between 2016-2020 recorded poor government performance in most of the indicators. The findings suggest a need to improve performance and efficiency in the public sector.